Effect of pine bark and compost on the biological denitrification process of non-hazardous landfill leachate: Focus on the microbiology - Trois, Cristina; Coulon, Frederic; Polge de Combret, Cécile; Martins, Jean M. F.; Oxarango, Laurent (Elsevier, 2010)
In an attempt to optimize the cost-efficiency of landfill leachate treatment by biological denitrification process, our study focused on finding low-cost alternatives to traditional expensive chemicals such as composted garden refuse and pine bark, which are both available in large amount in South African landfill sites. The overall objective was to assess the behaviour of the bacterial community in relation to each substrate while treating high strength landfill leachates. Denitrification processes in fixed bed reactors were simulated at laboratory scale using anaerobic batch tests with immature compost and pine bark. High strength leachate was simulated using a solution of water and nitrate at a concentration of 500 mg l−1. Results suggest that pine bark released large amounts of phenolic compounds and hydroxylated benzene rings, which both can delay the acclimatization time and inhibit the biological denitrification (only 30% efficiency). Furthermore, presence of potential pathogens like Enterobacter and Pantoea agglomerans prevents the applicability of the pine bark in full-scale operations. On the other hand, lightly composted garden refuse (CGR) offered an adequate substrate for the formation of a biofilm necessary to complete the denitrification process (total nitrate removal observed within 7 days). CGR further contributed to a rapid establishment of an active consortium of denitrifiers including Acinetobacter, Rhizobium, Thermomonas, Rheinheimera, Phaeospirillum and Flavobacterium. Clearly the original composition, nature, carbon to nitrogen ratio (C/N) and degree of maturity and stability of the substrates play a key role in the denitrification process, impacting directly on the development of the bacterial population and, therefore, on the long-term removal efficiency.
Keywords: Denitrification; Landfill leachate; Compost; Pine bark; Microbial diversity